Efektifitas Metode Coaching Dalam Pendidikan Dan Pelatihan Kepemimpinan Tingkat IV Angkatan II Dan III Di Pusat Pengembangan Sumber Daya Manusia Aparatur - Helmi, Ahmad (JURNAL APARATUR, 2019)
Regulation of the Head of National Institute of Public Administration (Lembaga Administrasi Negara: LAN) Number 13 year 2013 as amended by Regulation of the Head of National Institute of Public Administration Number 20 year 2015 on the Guidelines for the Implementation of Education and Training Program on Grade-IV Leadership Management mandates to apply other learning methods in addition to classical method, as: adviser (Coaching and mentoring) and counseling. One of the problems in implementing this education and training program is applying coaching method. Ineffective Coaching method can cause participants to be less motivated and the training output is not optimal. There are many methods of coaching, but what methods are most effective and efficient to apply in this Grade-IV leadership management education and training program? Study on the impact of Coaching methods for effective learning on participants in Education and Training Program on Grade-IV Leadership Management batch II and III year 2018 at the Human Resource Development Center for Apparatus, Ministry of Energy and Mineral Resources (MEMR), was conducted by using a qualitative approach. The discussion in this study is focused on what the effect of several Coaching methods for participants of Education and Training Program on grade-IV Leadership Management. Results show that Coaching is done through stimulation, powerful questions, and creative dialogue so that participants get the best achievement as expected. ABSTRAKPeraturan Kepala Lembaga Administrasi Negara (LAN) Nomor 13 Tahun 2013 yang telah diubah dengan Peraturan Kepala LAN Nomor 20 Tahun 2015 tentang Pedoman Penyelenggaraan Pendidikan dan Pelatihan (diklat) Kepemimpinan Tingkat IV mengamanatkan pelaksanaan metode pembelajaran selain dari pengajaran mata diklat dalam kelas, berupa: pembimbingan (coaching dan mentoring) dan konseling. Salah satu permasalahan dalam penyelenggaraan Diklat Kepemimpinan Tingkat IV adalah sejauh mana penerapan metode Coaching itu sendiri. Metode Coaching yang kurang efektif dapat menyebabkan peserta didik menjadi kurang termotivasi sehingga output diklat tidak optimal. Ada banyak sekali metode coaching, namun metode seperti apakah yang paling efektif dan efisien untuk digunakan dalam Diklatpim Tingkat IV ini? Penelitian tentang pengaruh metode coaching terhadap Peserta Diklat Kepemimpinan Tingkat IV Angkatan II dan III di Pusat Pengembangan Sumber Daya Manusia Aparatur, Kementerian Energi dan Sumber Daya Mineral (KESDM), dilaksanakan dengan menggunakan pendekatan kuantitatif deskriptif (campuran). Penelitian ini difokuskan pada pengaruh penerapan beberapa metode coaching terhadap peserta Diklat Kepemimpinan Tingkat IV. Hasil pene- litian menunjukkan bahwa metode coaching yang dilakukan melalui stimulasi, pertanyaan powerful, dan dialog kreatif mengarahkan peserta didik memperoleh prestasi terbaik seperti yang diharapkan.